The Process And Hegemony Effect Of Beauty Vloggers On University Student Behavior Of Using Cosmetics - Ayuningsih, Putri; Rahman, Abdul; Yuhastina, Yuhastina (The Journal of Society and Media, 2021)
Beauty vloggers and viewers become interesting business when cosmetic industry grows rapidly in Indonesia. Digital media are the most significant reason for the global cosmetic production, marketing and consumption reaching global society, especially female students. With limited funds, they should not always watch beauty vlog and buy cosmetics staffs. In facts, they are not aware of being consumers than being owners on beauty and cosmetic products businesses. The objective is to analyze the processes and impacts of the hegemony of beauty vlogger on students consuming cosmetics at Sebelas Maret University, Surakarta. We used Antonio Gramsci's hegemony theory. With qualitative approach, we collected data with interview students’ knowledges on cosmetic products and preferable vloggers or actors, observed students watching vlog, and documented membership, consumable beauty products discussion selected by 30 students as viewer/users. The validity of data used triangulation of sources and methods and then analyzed with Miles & Huberman technique. The results showed that the beauty vloggers hegemonize students’ viewers in several strategies: (1) increasing knowledge on cosmetics products and usages, (2) building trust to gain viewer’s sympathy, (3) intensifying communication with viewers, (4) creating local representatives for make-up and beauty, (5) regularly updating cosmetics data, inspiratory beauty creativity, and sale self-confidence. More students become beauty vlog viewers and users than beauty and cosmetic entrepreneurship owners.